Manajemen Media Massa dalam Mencegah Intoleransi Umat Beragama (Studi Kasus pada Koran Kedaulatan Rakyat Yogyakarta) - Daulay, Hamdan (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2021)
Religious intolerance often becomes a barrier in strengthening harmony in the country. The plurality that exists in society is indeed like a colorful flower in a garden that exudes beauty. When differences are managed properly, a harmonious atmosphere and mutual respect in amidst the existing differences will grow. However, when differences are interpreted as opponents and hostilities, intolerance and a prolonged conflict will emerge. Mass media management, through the news and opinions, has an important role in realizing a peacefull society. News that is honestly and objectively packaged will create peace. On the other hand, provocative reporting, slanders, and hoaxes will mislead people and raise conflicts for a plural society.Reports of religious intolerance in the mass media, including in the Kedaulatan Rakyat Yogyakarta, have become a serious concern for the editorial team. They try to make honest and objective news to avoid unrest in the society. The sensitive news about intolerance should not aggravate the situation that could invite conflicts. Cases of religious intolerance are sensitive and can easily cause reactions from the pros and cons of the news. The function of social control of media is to understand the emotional and psychological conditions of the conflicted people so that they can return to peace and respect each other with the differences.Â Keywords: harmony, intolerance, mass media management, hoaxes, peace message,Â the Kedaulatan Rakyat